Base pay and bonus pay for high-wage employees: A multi-study approach to organizational performance - Liana Bomm; Daniel Kaimann (Managerial and Decision Economics, 2022)
This paper studies how the compensation of high-wage workers is associated with organizational performance. Based on organizational justice arguments, cognitive evaluation theory (CET), and self-determination theory (SDT), we hypothesize that bonuses contingent on organizational performance tends to negatively impact the positive relationship between base pay and organizational performance. We use data from two distinct industry environments to show that the interaction between base pay and bonus pay is associated with reducing organizational performance for high-wage workers. More specifically, bonus pay relates to a decrease in the relationship between base pay and organizational performance.
Keywords: 650